Trypanosoma cruzi: Seroprevalence Detection in Suburban Population of Santiago de Querétaro (Mexico) - Ángeles López-Céspedes; Elena Villagrán; Kervin Briceño Álvarez; José Antonio de Diego; Hebert Luís Hernández-Montiel; Carlos Saldaña; Manuel Sānchez-Moreno; Clotilde Marín (The Scientific World Journal)
Objectives. To evaluate the potential of iron-oxide dismutase excreted (SODeCRU) by T. cruzi as the antigen fraction in the serodiagnosis of Chagas disease and compile new epidemiological data on the seroprevalence of this disease in the suburban population of the city of Santiago de Querétaro (Mexico). Design and Methods. 258 human sera were analyzed by the techniques of ELISA and Western blot and using the homogenate and the SODeCRU. Results. A total of 31 sera were positive against ELISA/SODeCRU (12.4%), while 30 sera proved positive by WB/SODeCRU (11.6%). The comparison between the technique of ELISA and WB showed a sensitivity of 93%, and a specificity of 99%. The positive predictive value was 93% and the negative predictive value was 99%, with a Kappa (κ) value of 1. Conclusions. These preliminary data reveal the degree of infection of nonrural areas of Mexico and demonstrated that SODeCRU is an antigen useful to diagnose Chagas disease.